Specialty competencies in clinical psychology - DiTomasso, Robert A. (Series in specialty competencies in professional psychology., 2013)
The field of psychology is witnessing a burgeoning competence movement and leading organizations have initiated major and sustained efforts to define and evaluate specific competencies in clinical psychology. In Specialty Competencies in Clinical Psychology, DiTomasso, Cahn, Panichelli-Mindel, and McFillin examine the need for competency-minded training in clinical psychology and provide a comprehensive overview of specific functional and foundational competencies in the specialty. Each chapter defines competence in specific functional domains such as assessment, case formulation, consultation.